THE CONCEPT OF PAPPASENG TELLU RIALA SAPPO IN PREVENTING INCEST BEHAVIOR THROUGH A MULTICULTURAL COUNSELING APPROACH - Rismiyana Rismiyana; Humairah Azzahra; Siti Nurhasmiah; Nur Fadhilah Umar (JURNAL NALAR PENDIDIKAN, 2023)
The implementation of the research is based on the number of cases of incest that occurred in South Sulawesi. The research aims to provide an overview of how the existence of pappaseng “Tellu Riala Sappo” can be used to prevent the emergence of incest behavior in the Bugis community of South Sulawesi. The method of this research is qualitative approach through a case study. The data collection consists of interview techniques and documentation studies. The Data Analysis was conducted for several stages. It consists of data reduction, data presentation, and conclusions. The performing data validation b using data triangulation. The results of data analysis point out that (1) the phenomenon of incest occurs in the Bugis people of South Sulawesi. Most of the incest cases that occur because of the perpetrator’s lack of self-control and religious understanding, so that they cannot contain their lust. (2) The existence of Pappaseng Tellu Riala Sappo in the Bugis community is only known by some people, and; (3) Pappaseng Tellu Riala Sappo contains religious values and self-control (Siri’) that can prevent the emergence of incest behavior in the Bugis people of South Sulawesi.